Tinea Favosa in A 7-Year-Old Indonesian Boy: A Rare Case Report - Michelle Wiryadana; Nova Zairina Lubis (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tinea favosa is an inflammatory infection of the skin, most often found on the scalp, caused by Trichophyton schoenleinii It is rarely reported and is more commonly found on immunocompromised patient, poor hygiene and nutrition, dense population, poverty, with limited access to healthcare. Transmission can occur directly from family members or close friends or indirectly through strands of infected hair or desquamation of affected epithelial. In this article, we reported a case of tinea favosa on a 7-year-old boy with itchy thick scale and mousy odor that occurred 2 months prior to medication. The patient responded well to oral antifungal (Griseofulvin) and antibiotic (amoxicillin) as well as topical treatment (fusidic acid cream, miconazole cream, and ketoconazole shampoo) after 6 weeks of treatment showing no dermatophyte growth on scalp scraping culture. Education of proper hygiene as well as reducing humidity on scalp area and improving the nutrition status are the main strategies to prevent the recurrence of this disease.